2012
DOI: 10.1021/am300784n
|View full text |Cite
|
Sign up to set email alerts
|

“Wetting Enhancer” Pullulan Coating for Antifog Packaging Applications

Abstract: A new antifog coating made of pullulan is described in this work. The antifog properties are discussed in terms of wettability, surface chemistry/morphology, and by quantitative assessment of the optical properties (haze and transparency) before and after fog formation. The work also presents the results of antifog tests simulating the typical storage conditions of fresh foods. In these tests, the antifog efficiency of the pullulan coating was compared with that of two commercial antifog films, whereas an untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 29 publications
1
92
0
Order By: Relevance
“…7-a). PLA-Lim15 ( This result suggested high transparency for films containing limonene and the possibility to see through the film is one of the most important requirements for consumers [41]. Negative values obtained for a* coordinate are indicative of a deviation towards green.…”
Section: Semmentioning
confidence: 83%
See 1 more Smart Citation
“…7-a). PLA-Lim15 ( This result suggested high transparency for films containing limonene and the possibility to see through the film is one of the most important requirements for consumers [41]. Negative values obtained for a* coordinate are indicative of a deviation towards green.…”
Section: Semmentioning
confidence: 83%
“…This behavior could be attributed to the limonene hydrophobic character. It has been reported that modifying the physicochemical properties of the material surface can control the water adsorption [41]. Therefore, PLA films containing limonene are also expected to have higher resistance to water adsorption than neat PLA film.…”
Section: Wettabilitymentioning
confidence: 99%
“…The manipulation of surface wettability through a combination of chemical and structural modifications has been of recent interest for a variety of applications such as anti-fog surfaces [8][9][10]. The "fog phenomenon" describes the condensation of water vapor to small drops that are dispersed on a solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…In all examples mentioned, fog causes a reduction in the light transmission, hence damaging the visibility of the products. In food packaging, the esthetics of the package is damaged, and the quality of the food may decrease to the point where it can no longer be sold due to the accumulated moisture [8,11]. In agricultural films, the fog droplets reduce light transmission and inhibit the growth of crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation